Radionuclide accumulation by objects of ecosystem - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Botova, M. A.; Fedorets, I.D. (Вопросы атомной науки и техники, 2014)
The isotope contents of family uranium and thorium in the ash of wood of trees and pine needles before and after
leaching by water were measured. The element contents in the ash of wood of trees and pine needles were measured
by γ-activation analysis and spectrophotometer. A significant excess of lead-210 in pine needles in the vicinity of
thermal power plant relatively its average content in Ukraine was discovered. Differences of magnitude of leaching
uranium series isotopes, ¹³⁷Cs and ⁴⁰K from the wood of trees and pine needles were defined, which is due to the
different character of the formation of crystallites during ashing of these objects Проведены измерения содержания изотопов ряда урана и тория в золе деревьев и хвои сосны до и после выщелачивания водой. Измерено содержание элементов в золе деревьев и хвое сосны при помощи γ-активационного анализа и спектрофотометрии. Обнаружено значительное превышение содержания свинца-210 в хвое сосны в районе тепловой электростанции относительно его среднего содержания в Украине. Обнаружены различия величины выщелачивания изотопов ряда урана, ¹³⁷Cs и ⁴⁰K из деревьев и хвои сосны, которые обусловлены разным характером формирования кристаллитов при озолении в этих объектах. Проведено вимiрювання вмiсту iзотопiв ряду урану i торiю в золi дерев i хвої сосни до i пiсля вилуговування водою. Вимiряно вмiст елементiв в золi дерев i хвої сосни за допомогою gamma;-активацiйного аналiзу та спектрофотометрiї. Виявлено значне перевищення вмiсту свинцю-210 в хвої сосни в районi теплової електростанцiї щодо його середнього вмiсту в Українi. Виявленi вiдмiнностi величини вилуговування iзотопiв ряду урану, ¹³⁷Cs i ⁴⁰K з дерев i хвої сосни, якi обумовленi рiзним характером формування кристалiтiв при озоленнi в цих об'єктах.